The Effects of Conflict and Palm Oil Investment Between Investors and Communities in Indonesia - Rahmad HENDRA; Rosa AGUSTINA; Ratih LESTARINI (Indonesia Strategic Sustainability, 2023)
The resolution of customary land conflicts often does not bring results. The protracted conflict inflicted losses on both sides. The community cannot benefit from the land that is their customary right because it is under the control of the Oil Palm Plantation Company (PPKS), while PPKS cannot operate comfortably because it must always face community demands. Until now, there are still conflicts in oil palm plantations that occur between indigenous peoples in Kampar Regency, Riau Province and PPKS. Based on these conditions, the legal issue that is also the main problem in this study is why there is a land conflict between oil palm plantation business investors and indigenous peoples and how the parties resolve it. The author found that the conflict occurred due to differences in views on customary land, the non-implementation of deliberations with indigenous peoples before investment was made, and government policies. Conflict resolution is carried out using different means according to the cause of the conflict.